Ketidakpatuhan Sudan Selatan dalam Skema Perjanjian Internasional R-ARCSS Terkait Keterlibatan Tentara Anak dalam Angkatan Bersenjata - Fithria, Farah Agnis (INTERDISCIPLINARY JOURNAL ON LAW, SOCIAL SCIENCES AND HUMANITIES, 2024)
This article aims to discover and understand the reasoning behind actor noncompliance with international agreements. In this case, the Government of South Sudan is not in compliance with international igreements relating to the involvement of child soldiers in the armed forces. International agreements seek to bind members to rules agreed upon by each party. This article discusses the R-ARCSS Agreement, signed by the two parties who previously clashed in the civil war in South Sudan and mediated by the UN and IGAD. This research examines the regulations that South Sudan does not comply with, especially regarding the involvement of child soldiers in the armed forces. The research question for this article is, "Why does South Sudan continue to recruit child soldiers despite having signed the R-ARCSS agreement?" This research uses qualitative methods with a noncompliance theory approach, where three variables illustrate the reasoning for South Sudan’s noncompliance with international agreements, as seen from the unclear provisions in the agreements. These give rise to multiple interpretations (ambiguity), the existence of limited capacity to comply with rules or regulations (capacity limitations), and changes in domestic conditions (temporal dimensions). Keywords: International Agreement, Child Soldiers, Armed Force, South Sudan, Non-compliance Theory